(untitled) (Research, Society and Development, 2024)
The present study aimed to examine the physiological and psychological benefits of dance, as well as its effects on children and adolescents. We also analyzed the types of dance applied in disciplines and the methodologies used, investigating dance as a different modality to promote greater physical activity. The research was carried out based on studies published in the last two decades in renowned databases, such as PubMed, MEDLINE and Web of Science, considering only peer-reviewed articles in English. The results indicated that dance is an effective alternative to traditional forms of physical activity, providing benefits for both the healthy population and those with clinical impairments. The adoption of dance-based programs requires recognition as a health promotion strategy, as well as financial and political support for its implementation. The conclusions highlight the need for integrated changes in public health policies, including encouraging debate and formulating specific legislation that incorporates dance as a complementary modality. Such measures increase its impact as a tool for promoting public health, demonstrating its relevance for improving the quality of life on various issues.